Changing patterns of trade and global value chains in postcrisis Asia. - Wignaraja, Ganeshan (ADB briefs., 2017)
This brief examines changing patterns of trade and global value chains (GVCs) in developing Asia, focusing on the period since the crisis. It analyzes the export slowdown in real terms and in relation to real GDP growth for the region and for major economies. It then attempts to explain the export slowdown. Finally, it considers emerging new trading opportunities in the region and policy suggestions.